(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
The purpose of this study is to investigate the process of creative thinking in VIII class in solving space build of the flat side problems based on Wallas stages reviewed by student”s Adversity Quotient (AQ). This study used a qualitative descriptive method. Subjects were determined through purposive sampling which is based on several criteria, namely : (1)in the category of adversity quotient to be analyzed (climber,camper,quitter) and (2) have good communication skills (based on information from the teacher). Finally, subjects were taken for this research is 1 person for each category of AQ. The techniques of collection the data was done by doing task-based interview. The task in this research is Test of Problem Solving. The data analysis techniques include three activities there are classification, data presentation and conclusion. Data validation was done by time triangulation and perseverance. Based on the results of data analysis, it can be concluded that the creative thinking process of student climber,camper and quitter at each stage Wallas.